Transient Effects at Power-Supply System of the Czech Railways from EMC Viewpoint - Dolecek, Radovan; Hlava, Karel (Radioengineering Society, 2007)
The paper deals with the behavior of the traction power-supply system 25 kV, 50 Hz at the Czech Railways. Electrical conditions on a contact line affect electrical conditions in a feeding station. This relation represents galvanic coupling from EMC viewpoint. Explanation of transient effects during short-circuits at the contact line can be considered as the main problem. These effects can arise during a failure in a traction circuit. Therefore, the attention is turned to an adjustment protection design of the traction circuit. Simulation diagrams were created. The design can be utilizable for a feeding station with Filter-Compensation Equipment, which is designed for the EMI reduction.
Keywords: Power-supply system; power supply line; Filter-Compensation Equipment; feeding station; contact line; transient effect; harmonic branch; short-circuit